2021
DOI: 10.1080/23311932.2020.1862469
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition and sensory quality of injera prepared from tef (Eragrostis tef (Zucc.) Trotter) complemented with lupine (Lupinus spp.)

Abstract: Nutritional composition and sensory quality of injera prepared from tef (Eragrostis tef (Zucc.) Trotter) complemented with lupine (Lupinus spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…The blend of oats and stinging nettle, lupine and stinging nettle, and the gross energy values have a statistically significant (p < 0.05) relationship. This study disagreed with the findings of Yegrem et al. (2021) , who showed the increments of calorific energy in injera from 393.8 to 400.4 kcal/100 g upon 20% lupine flour addition with tef flour.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The blend of oats and stinging nettle, lupine and stinging nettle, and the gross energy values have a statistically significant (p < 0.05) relationship. This study disagreed with the findings of Yegrem et al. (2021) , who showed the increments of calorific energy in injera from 393.8 to 400.4 kcal/100 g upon 20% lupine flour addition with tef flour.…”
Section: Resultscontrasting
confidence: 99%
“…In this study, 15% lupine was blended to achieve the best overall sensory acceptance of the final fermented beverage. A similar result was also reported by Yegrem et al. (2021) .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the top surface of injera, baked even without absit, there are fewer eyeballs (pits) which shows in ( Figure 2 ) below. The number of larger eyeballs on the upper surface determines the attractiveness of injera [ 56 ]. Aflegna is a delicious injera that has been cooked after only 24 hours of fermentation.…”
Section: Injera Fermentationmentioning
confidence: 99%
“…), followed by Europe which comfortably occupies second place (32.1%, 396 k ha), then Africa (5.4%, 66 k ha), with America having close data (4.6%, 57 k ha); in last place is Asia (<1%, 108 ha). From the geographical point of view, it is possible to group the included articles by origin continents: Europe [ 50 , 51 , 53 , 55 , 59 , 63 , 70 , 72 , 73 , 75 ], South America [ 54 , 58 , 61 , 66 ], Asia [ 47 , 56 , 60 , 64 , 65 , 68 , 69 , 74 , 77 , 78 ], Africa [ 49 , 52 , 62 , 67 , 71 , 76 , 79 ] and Oceania [ 48 , 57 ]. This grouping revealed that Europe and Asia are, for now, the leading promoters of these novel food products, and Africa also reports many studies.…”
Section: Discussionmentioning
confidence: 99%